PENGEMBANGAN MEDIA ADOBE FLASH BERBASIS KONTEKS LUBUKLINGGAU DITINJAU DARI SEGI KEVALIDAN - Lissa Anggraini; Rani Refianti; Idul Adha (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2021)
This study aims to produce a context-based mathematics learning media in Lubuklinggau using a valid Adobe Flash application. This research is a development research using the ADDIE model. This model consists of 5 stages, namely: the analysis stage (Analyze), planning (Design), development (Development), implementation (Implementation), and evaluation (Evaluation). Data collection was carried out using a questionnaire sheet and a walkthrough. Based on the results of the assessment analysis by three experts, namely: linguists, material experts, and media experts, it showed that the Lubuklinggau context-based mathematics learning media using the Adobe Flash application met the valid criteria with an average score of 4.05.